Family Time and Family Structure as Correlates of Adolescents’ Self-Regulation in some Selected Junior Secondary Schools, Harari Regional State, Ethiopia - Amare Misganaw Mihret (Bina Nusantara University, 2019)
This research aimed to examine the relationship between family time and family structure with adolescents’ self-regulation in some selected Junior Secondary Schools, Harari Regional State, Ethiopia. To run on, data were collected through selfreporting questionnaire, standardized tests from 325 students selected through systematic sampling method. The data analysis was conducted using a t-test, Pearson product moment correlation, factorial ANOVA, and multiple regression. This research indicates that adolescents have a slightly lower level of self-regulatory behavior. There is a statistically significant relationship between adolescents’ self-regulation and family time, family structure, and family time activity. Family time activity especially those who have leisure or recreation time together has significantly influencing adolescence self-regulation; however, gender could not make such effect independently as well as in combination with family time activity. Moreover, among others, family time activity and family structure are found to be important predictors of adolescents’ self-regulatory skills. Among the variability, family time activity significantly has added to the prediction of self-regulation, accounting for 14,8% of the variability, while, family time activity and family structure together have added 17,7% of the variability. In the end, recommendations are also made for how to properly address the gaps noted in this research.